Effectiveness of Aromatic Plants on The Population and Intensity of Aphis gossypii Pest Attack on Plant Cucumis sativus - Rika Ningtias,; Nanang Tri Haryadi, (Jurnal Online Pertanian Tropik, 2023)
The control of plant-disturbing organisms particularly in cucumber plant pests, such as the aplications of chemical and vegetable pesticides. The use of chemical pesticides dosis that is determined made the pests more resistent than normal dosis. Reduction of chemical pesticides can be done with a polyculture cropping system using aromatic plants. The purpose of this study was to determine the effect of aromatic plants on population, intensity of pest attacks, and production yields in cucumber plants, then find out the most effective treatment to suppress populations of pest. This research conducted in Tanjung Rejo Village, Wuluhan District, Jember in January to July 2021. The research design used a randomized block design with 4 treatments that is P0 (control), P1 (basil), P2 (leek), and P3 (celery) which is repeated 6 times. The observed variabels were the population of pest, intensity of pest attaks, and cucumber productions. The data obtained were tested with ANOVA and if it were significantly different, further tests were carried out using Duncan Multiple Range Test with a level of 5%. Based on the result of this study, it showed that the types of aromatic plants has an effect on Aphis gossypii pests in cucumber plants with significantly different effects every week. The highest population and intensity of pest damage in P0 (control) treatment is 32,91 tails/ plants and intensity of pest damage is 21,08 %/ plants. The most effective treatment that can suppress the population of pest in basil treatment is 20,48 tails/plant and intensity of pest damage is 15,69 %/plants. The highest cucumber production in the basil treatment is 10,25 tons/Ha and the lowest cucumber production in the control treatment is 8,5 tons/Ha.